Anti-Fraud and Anti-Corruption Tools in the Struggle Against Fraudulent Acts in the Public Sector - Gökçe Sinem Erbuğa (Muhasebe Enstitüsü Dergisi)
This study reveals the implications of anti-fraud and anti-corruption policies in the struggle against public sector accounting fraud and addresses the effectiveness of a vast number of methods for detecting fraudulent acts. This study also focuses on the terms and concepts of public sector fraud and corruption in order to provide a better understanding of the fraudulent acts committed within the public sector. This study’s essential research aims are directed toward deterring the fraudulent actions of organizations (both government and state-owned enterprises [SOEs]) from the public sector’s viewpoint and their financial results. In summary, the study deals with how to prevent fraudulent acts that are likely to be carried out and aims to provide a better understanding of the methods used to detect fraud and corruption in the public sector.